2000
DOI: 10.1093/humrep/15.12.2669
|View full text |Cite
|
Sign up to set email alerts
|

The management of mature cystic teratomas in children and adolescents: a retrospective analysis

Abstract: Mature cystic teratomas (MCT) are the most common ovarian tumours seen in children and adolescents. Fifty-two patients <21 years of age had surgical removal of an MCT, 14 of whom were approached laparoscopically. Compared with laparotomy, those patients managed laparoscopically had a significantly shorter hospital stay. Intra-operative tumour spillage occurred in 27 (52%) patients; there were no cases of chemical peritonitis. Available follow-up data on 34 (65%) patients revealed seven pregnancies occurring at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
81
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 21 publications
1
81
1
5
Order By: Relevance
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In fact the mean operative time in our experience (64 min) is similar to that reported by Volz et al [10], who used a similar technique, and by Yuen and Rogers [20] (60 min) and Morgante et al [58] (57 min) for open surgery and by Pardi et al [42] for laparoscopy-assisted vaginal removal, but it was lower than what was reported by other authors for laparotomy [18,21,22] or laparoscopy (table 2), [8,9,12,18,19,20,21,22,26,27,29,33,34,36,37,39,40]. Our mean surgical time is also lower than that reported by Ferrari et al [38] or Wang et al [44] for the direct vaginal approach (81 and 78 min, respectively).…”
Section: Discussionsupporting
confidence: 88%
“…Until recently, dermoid cysts were removed by laparotomy, but nowadays there is really no safe method to avoid spillage, particularly when performing a cystectomy. In fact, dermoid cysts with a thin capsule can often not be enucleated without rupture even by laparotomy [13,16,17,18,19,20,21,22]. Manyonda et al [23] suggested to perform a microlaparotomy to remove dermoid cysts intact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 Most surgeons agree on the use of laparoscooy when a young female patient complains of vague lower abdominal pain and there are many reports showing that laparoscopy improves diagnosis and provides proper therapeutic option. 23 In our study, among the 5 patients with Adnexal Mass, 3 patients had laparoscopic aspiration followed by excision of the cystic masses.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito que representan a 38% de las neoplasias del ovario y 57% de los tumores germinales en las niñas y adolescentes (12,15,18,19). No se ha descrito degeneración maligna de un teratoma maduro en niñas, aunque existe un 1-2% de ellos que sufre transformación maligna del componente epitelial en las mujeres adultas.…”
Section: Discussionunclassified